Recent Advances in Measurement and Dietary Mitigation of Enteric Methane Emissions in Ruminants - Patra, Amlan K. (Frontiers in Veterinary Science, 2016)
Methane (CH4) emission, which is mainly produced during normal fermentation of feeds by the rumen microorganisms, represents a major contributor to the greenhouse gas (GHG) emissions. Several enteric CH4 mitigation technologies have been explored recently. A number of new techniques have also been developed and existing techniques have been improved in order to evaluate CH4 mitigation technologies and prepare an inventory of GHG emissions precisely. The aim of this review is to discuss different CH4 measuring and mitigation technologies, which have been recently developed. Respiration chamber technique is still considered as a gold standard technique due to its greater precision and reproducibility in CH4 measurements. With the adoption of recent recommendations for improving the technique, the SF6 method can be used with a high level of precision similar to the chamber technique. Short-term measurement techniques of CH4 measurements generally invite considerable within- and between animal variations. Among the short-term measuring techniques, Greenfeed and methane hood systems are likely more suitable for evaluation of CH4 mitigation studies, if measurements could be obtained at different times of the day relative to the diurnal cycle of the CH4 production. Carbon dioxide and CH4 ratio, sniffer and other short-term breath analysis techniques are more suitable for on farm screening of large number of animals to generate the data of low CH4 producing animals for genetic selection purposes. Different indirect measuring techniques are also investigated in recent years. Several new dietary CH4 mitigation technologies have been explored, but only a few of them are practical and cost-effective. Future research should be directed towards both the medium- and long-term mitigation strategies, which could be utilized on farms to accomplish substantial reductions of CH4 emissions and to profitably reduce carbon footprint of livestock production systems. This review presents recent developments and critical analysis on different measurement and dietary mitigation of enteric CH4 emissions technologies.